Velocity-based training and autoregulation applied to "squatting every day" - Bryant Martinez, D.; Kennedy, C. (Journal of Australian Strength and Conditioning, 2016)
The purpose of this case study was to investigate the efficacy of performing strength training specific to squatting movements with very high-frequency; or as it is stated commonly "squatting every day"(1). The subject used velocity-based training and autoregulation to perform a specific squatting variation to a daily one-repetition maximum, followed by training loads corresponding to that daily one-repetition maximum, every day for the month of January 2015. In the last training session of this study the subject performed an all-time personal record of 182-kilograms in the belted back squat; an improvement of 4-kilograms (2.3%) over his best all-time squatting performance across 8-years of competitive Olympic Weightlifting. This was also an improvement of 26-kilograms (16.7%) over the month of January from the first belted back squat testing session performed on day 3 of the program (156-kilograms). Squatting with very high-frequency appears to be an effective use of a short strength training cycle specific to the development of one-repetition maximum strength. Practical limitations exist for the vast majority of training populations due to the general and specific demands common to both team and individual sport athletes. When appropriate, high-frequency training may be beneficial to athletes during a period of reduced competitive demands where training resources can be dedicated to the development of more singular training qualities.